Snow White with the red hair. 11 - Akiduki, Sorata (Shojo beat manga., 2021)
"Shirayuki is an herbalist famous for her naturally bright-red hair, and the prince of Tanbarun wants her all to himself! The prince from the neighboring kingdom, Zen, rescues her from her plight, and thus begins their love story ... Yuzuri, Suzu, and Kirito travel all the way from Lilias to visit Shirayuki and friends, resulting in a delightful reunion, until the chief throws a wrench in their plans! Meanwhile, Izana pressures Zen to hold a banquet to seek out potential brides, but Zen has another idea in mind."--Provided by publisher